2021
DOI: 10.3390/min11020148
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Machine Learning Applications in Mining: Exploration, Exploitation, and Reclamation

Abstract: Recent developments in smart mining technology have enabled the production, collection, and sharing of a large amount of data in real time. Therefore, research employing machine learning (ML) that utilizes these data is being actively conducted in the mining industry. In this study, we reviewed 109 research papers, published over the past decade, that discuss ML techniques for mineral exploration, exploitation, and mine reclamation. Research trends, ML models, and evaluation methods primarily discussed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 121 publications
0
29
0
8
Order By: Relevance
“…By studying statistical reports shared by mining departments, we concluded that mining accidents occurred in the past due to poor supervision, inadequate implementation of enactment, lack of security consciousness, and inadequate safety education (Jung & Choi, 2021). What are the factors which make mining threatening?…”
Section: Resultsmentioning
confidence: 99%
“…By studying statistical reports shared by mining departments, we concluded that mining accidents occurred in the past due to poor supervision, inadequate implementation of enactment, lack of security consciousness, and inadequate safety education (Jung & Choi, 2021). What are the factors which make mining threatening?…”
Section: Resultsmentioning
confidence: 99%
“…As pointed out before, in a systematic review, the main objective is to investigate the body of knowledge to address a set of research questions [42,43]. This must be done using concrete methods and procedures for the sake of transparency and ease of evaluating the objectivity and trustworthiness of the figures and outcomes reported for the potential readers [42].…”
Section: Main Research Questions and Review Methodsmentioning
confidence: 99%
“…78/2010 on Reclamation and Post-Mining [18], an effective reclamation program and reforestation of post-mining land are stated clearly, even with the closure of the mine [10]. Reclamation is the last stage in mining activities after the exploration and exploitation stages [19]. In this paper, the terminology of reclamation refers to activities to improve post-mined land conditions so that they can function again as originally intended or according to other productive uses that have been planned [20].…”
Section: Law and Regulation Of Mining In Indonesiamentioning
confidence: 99%